Screening for Opioid and Stimulant Exposure In Utero Through Targeted and Untargeted Metabolomics Analysis of Umbilical Cords. Issue 5 (October 2020) - Mamillapalli, Srivalli Swathi; Smith-Joyner, Annalisa; Forbes, Lauren; McIntyre, Kadesha; Poppenfuse, Samantha; Rushing, Blake; Strom, Cody; Danell, Allison S.; May, Linda; Kuehn, Devon; Kew, Kimberly; Ravisankar, Srikanth
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Neonatal abstinence syndrome is an array of signs and symptoms experienced by a newborn due to abrupt discontinuation of intrauterine exposure to certain drugs, primarily opioids. In the United States, the incidence of neonatal abstinence syndrome has tripled over the past decade. The current standard of care for drug testing includes the analysis of infant urine and meconium. Sample collection is associated with several limitations, including diaper media interferences, limited sample amount, sample heterogeneity, and the need for professional staff for collection. Umbilical cord tissue has emerged as a convenient sample matrix for testing owing to its universal availability. The purpose of this study was to examine umbilical cords using an untargeted metabolomics approach to determine the detected drugs and validate an analytical method to confirm and quantify the identified drugs. Methods: A metabolomics analysis was performed with 21 umbilical cords to screen for drugs and drug metabolites by liquid chromatography–mass spectrometry. Drugs were identified using the National Institute of Standards and Technology database, and an analytical method was developed and validated using secondary liquid chromatography–mass spectrometry instrument for positive confirmation and quantitative analysis. Results: Twenty-one random umbilical cords from women were tested: 4 were positive for cocaine and the primary and secondary metabolites; one was positive for methadone, the primary metabolite; 3 were positive for cotinine, the metabolite of nicotine; and 5 were positive for acetyl norfentanyl. Conclusions: Our research is a prospective method development study using untargeted and targeted approaches to characterize steady-state drug metabolite levels in the umbilical cord matrix at the time of delivery. By characterizing drug type and concentration, this methodology can be used to develop a reliable complementary testing method for meconium toxicology screens.